2000
DOI: 10.1053/he.2000.6496
|View full text |Cite
|
Sign up to set email alerts
|

Survivin promotes cell proliferation in human hepatocellular carcinoma

Abstract: Survivin is a recently described inhibitor of apoptosis. Because suppression of apoptosis is important for carcinogenesis and tumor growth, we investigated the expression and function of survivin in human hepatocellular carcinomas (HCCs). We have shown that 4 HCC cell lines and 7 out of 8 human HCC tissues expressed survivin messenger RNA (mRNA), whereas expression of survivin mRNA was not detected in normal liver and nontumor areas of these tissues using the reverse transcription polymerase chain reaction. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
266
2
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(291 citation statements)
references
References 23 publications
21
266
2
2
Order By: Relevance
“…This evidence could justify the poor prognosis of human cancer with high cytoplasmic Survivin expression (Adida et al, 1998b;Swana et al, 1999;Ito et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence could justify the poor prognosis of human cancer with high cytoplasmic Survivin expression (Adida et al, 1998b;Swana et al, 1999;Ito et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence on the molecular mechanism also showed that survivin prompted proliferation of HCC cells. 15 On the one hand, survivin has an important role in the regulation of cell division, however, on the other hand survivin, as a member of the inhibitory apoptosis family, exerts the capability of antiapoptosis and the reduced sensitization of cancer cells to chemotherapy and radiotherapy. 23 Compared with non-HCC cells, HCC cells are more sensitive to the loss of survivin function because of the higher expression of survivin.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, our result was consistent with the results of a previous clinical study that survivin expression in HCC tissues strongly correlated with the proliferation index, but did not significantly correlate with the apoptosis index. 15 A recent study has shown that adenovirus could be a promising delivery system to express anti-survivin hammerhead ribozymes in vivo. 33 In our in vivo study, adenovirus-mediated survivin shRNA was intratumorally injected in nude mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IAPs, which were first found in baculoviruses, are classified into five types, IAP1 through IAP5, according to their sequence homology (Luque et al 2001). In recent years, svv has been studied in many mammalian species, such as humans, guinea pigs and mice (Ito et al 2000;Habtemichael et al 2010;Stauber et al 2006). Previous studies have shown that svv is abundantly expressed in human cancers but is almost absent from normal differentiated cells (Ambrosini et al 1997).…”
Section: Introductionmentioning
confidence: 99%